PROSPECTIVE STUDY OF COMPLETE ACROMIOCLAVICULAR JOINT DISLOCATION REPAIR BY DOUBLE ENDOBUTTON METHOD - Mohanty, Rashmiranjan; JENA, ARPITA (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Double-endobutton technique offers a better treatment for dislocation when compared to conventional method for the acromioclavicular (AC) joint disturbance treatment. Hence, we have planned to assess the experimental outcomes of complete AC joint dislocation through double endobutton method. Methods: Thirty subjects among 20–68 years with a complete AC joint dislocation were studied. Diagnosis has been made by radiograph of both clavicle anteroposterior stress view and all subjects were subjected to Double Endobutton practice. Outcome was assessed using visual analog score, disabilities of the arm, shoulder, and hand, coracoclavicular, and constant shoulder score. Results: Among 30 subjects, male subjects were found to be 18 subjects with 34.43±7.65 years as the mean age between them. There was a substantial decrease in VAS score and DASH score from pre-operative to post-operative. A substantial development in the subjective shoulder value (28.4% vs. 98.12%; p=0.001) and Constant–Murley score (32.43% vs. 96.76%; p=0.005) from pre-operative to post-operative was observed with the subjects. At final follow-up, 28 patients showed excellent outcome and fair outcome in two patients. Further, no subjects were reported with any additional difficulties. Conclusion: This practice offers a modest, affordable, single-stretch surgical procedure that re-establishes coraco-clavicular interval and sustains until the native ligaments rebuild. This technique also demonstrates to be an outstanding alternate modal in rectifying whole AC joint dislocation.